ANALYSIS OF SPEECH ACTS AND IMPLICATURE IN THE POLITICAL ADVERTISING OF CANDIDATES LEGISLATIVE MEMBERS BOJONEGORO DISTRICT 2019 - Asror, Abdul Ghoni (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This study aims to describe and explain: 1) the forms of conversational implicated in Political Advertising of Candidates for Legislative Members 2019 and 2) the purpose of the conversational implicate of Political Advertising for Candidates for Legislative Members in 2019. The data collection used in this research is the listening and note technique. Data analysis uses content analysis techniques while the data validation technique uses data source triangulation and theory triangulation. The results of the discussion show that there are four forms of speech acts that are implicated in the Political Advertising Discourse of Candidates for the 2019 Legislative Members in the form of representative, directive, expressive, and commissure. Found as many as seven goals of the implicated in the Political Advertising Candidates for 2019 Legislative Members, namely, expressing hope, making proposals, giving advice, inviting to do something, showing feelings, and promising, so that the legislative candidates can attract the sympathy of their voters.